Field research 2013 - Kansas State University. Agricultural Experiment Station and Cooperative Extension Service (Kansas Agricultural Experiment Station Research Reports, 2013)
Includes research reports from these locations: East Central Kansas Experiment Field. Kansas River Valley Experiment Field, and Kansas State University Department of Agronomy.
Keywords: Kansas Agricultural Experiment Station contribution; no. 13-243-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1084; Kansas; Agriculture; Crops; Weed control; Disease control; Fertilizer; Irrigation